Penanganan Manajemen Isu Penutupan Media Penyiaran - Rahmatulah, Dimas (Program Studi Ilmu Komunikasi UII, 2024)
Broadcast media such as radio face significant challenges in the digital era, including the issue of broadcast closure, as experienced by Trax FM Jakarta. This research aims to understand the response of the public relations team in managing the crisis, using the case of Trax FM Jakarta. The research employs a qualitative approach with a case study strategy. Data was collected through observation and interviews. The results show that the Trax FM public relations team took steps to manage the crisis by communicating to the public that Trax FM was not closing but changing its broadcast format. Additionally, it was communicated that Trax FM Jakarta’s songs could still be streamed at traxonsky.com. With such issue management, the Trax FM public relations team could better mitigate the closure issue in the community.